THE FUTURE OF LIBRARIES: HOW TO FIGURE OUT WHAT AWAITS US - Умида Вахобова (Web of Journals Publishing, 2025)
The article discusses current trends in the development of libraries in the context of digitalization of society. It analyzes changes in the role of libraries, the emergence of new services and technologies, as well as the continuing mission of libraries as centers of knowledge, culture and social integration.
Keywords: Libraries, digitalization, innovation, social mission, information technology, cultural heritage.